2003
DOI: 10.1063/1.1564642
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent magnetic force microscopy investigation of epitaxial MnAs films on GaAs(001)

Abstract: We present variable-temperature magnetic force microscopy ͑VT-MFM͒ studies of epitaxially grown MnAs films on GaAs͑001͒. Around a critical temperature of T c ϭ40°C, the MnAs film undergoes a first order structural phase transition. Due to the strain involved, ferromagnetic ␣-MnAs and paramagnetic ␤-MnAs phases coexist as stripes along MnAs͓0001͔. The dimensions of the ␣-phase change from isolated dots at higher temperatures to well ordered stripes at lower temperatures. VT-MFM allows a close look at the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 12 publications
1
52
0
Order By: Relevance
“…Nanocomposites with ferromagnetic above room temperature MnAs nanoclusters, embedded in GaAs matrix (MnAs/GaAs), are promising candidates for this type of material (e.g. [1][2][3]). Recently, it has been reported that thermal annealing of Ga 1−x Mn x As layers leads to formation of MnAs dots (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites with ferromagnetic above room temperature MnAs nanoclusters, embedded in GaAs matrix (MnAs/GaAs), are promising candidates for this type of material (e.g. [1][2][3]). Recently, it has been reported that thermal annealing of Ga 1−x Mn x As layers leads to formation of MnAs dots (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of a very large and anisotropic lattice misfit, MnAs can be epitaxially grown on GaAs(001) in good quality [2]. While the bulk MnAs shows the first-order phase transition from the ferromagnetic, hexagonal -phase to the paramagnetic, orthorhombic -phase at 313 K, -MnAs and -MnAs coexist in MnAs films epitaxially grown on GaAs(001) over a certain temperature range via the strain stabilization [3]- [7]. It is well known that the coexisting -MnAs and -MnAs phases form a self-aligned stripe structure with varying periodicity depending on the film thickness.…”
mentioning
confidence: 99%
“…The temperature-dependent atomic force microscopy (AFM) and MFM show that the morphology and the structure of films are strongly correlated with the magnetic structure [3]. Low-energy electron microscopy (LEEM) and X-ray magnetic-circular-dichroism photo emission electron microscopy (XMCDPEEM), which allows a direct mapping of the in-plane magnetization, were combined to investigate the micromagnetic properties with a high lateral resolution [4].…”
mentioning
confidence: 99%
“…In spite of a very large and anisotropic lattice misfit, MnAs can be epitaxially grown on GaAs(001) in good quality [2]. While the bulk MnAs shows the first-order phase transition from the ferromagnetic, hexagonal -phase to the paramagnetic, orthorhombic -phase at 313 K, -MnAs and -MnAs coexist in MnAs films epitaxially grown on GaAs(001) over a certain temperature range via the strain stabilization [3]- [7]. It is well known that the coexisting -MnAs and -MnAs phases form a self-aligned stripe structure with varying periodicity depending on the film thickness.…”
mentioning
confidence: 99%
“…The temperature-dependent atomic force microscopy (AFM) and MFM show that the morphology and the structure of films are strongly correlated with the magnetic structure [3]. Low-energy electron microscopy (LEEM) and X-ray magnetic-circular-dichroism photo emission electron microscopy (XMCDPEEM), which allows a direct mapping of the in-plane magnetization, were combined to investigate the micromagnetic properties with a high lateral resolution [4].…”
mentioning
confidence: 99%